Reading key jazz rhythms for alto saxophone in Eb and baritone saxophone / für Altsaxophon in Es and Baritonsaxophon - Lipsius, Fred 1943- (Advance Music Products, 1996)
"Contains 24 etudes with the corresponding CD track numbers indicated for both the listening and play-along versions"--P. 6.
Play along
Keywords: Jazz -- Instruction and study; Etüde; Jazz; CD-ROM; Instrumentalmusik